THE EFFECT OF ECONOMIC GROWTH REGIONAL ORIGINAL INCOME GENERAL ALLOCATION FUND AND SPECIAL ALLOCATION FUND ON CAPITAL EXPENDITURE IN DISTRICT/CITY IN NORTH SUMATRA PROVINCE - M. Firza Alpi (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to determine the effect of economic growth, local revenue, general allocation funds and special allocation funds on capital expenditures in regencies/cities in the province of North Sumatra. This research is a type of associative research. The sampling technique was carried out using a purposive sampling technique. So that the sample obtained is 31 regencies/cities in the province of North Sumatra with a total of 165 observational data for 5 years of observation. The data collection technique used is documentation with data sources using secondary data taken through the official website of the Ministry of Finance DJPK. The data analysis technique used in this study is multiple linear regression analysis with SPSS 26 software tools. The results of this study indicate that economic growth has no effect on capital expenditures. Local revenue does not have a significant effect on capital expenditure. General allocation funds have a significant effect on capital expenditures. Special allocation funds have a significant effect on capital expenditures. Then economic growthlocal revenue, general allocation funds and special allocation funds andeffect on capital expenditure simultaneously.Keywords: Economic Growth, Regional Original Income, General Allocation Fund, Special Allocation Fund, Capital Expenditure.